Liquidity, Leverage, and Profitability: Their Impact on Corporate Tax Aggressiveness - Made Mutiara; Naniek Noviari (Fakultas Ekonomi dan Bisnis Universitas Udayana, 2026)
Tax aggressiveness involves both legal and illegal actions taken by companies to minimize their tax liabilities. Key characteristics such as liquidity, leverage, and profitability are believed to influence the extent of tax aggressiveness. This study investigates the impact of profitability, liquidity, and leverage on tax aggressiveness in property and real estate companies listed on the Indonesia Stock Exchange during the 2020–2022 period. The analysis and interpretation of the study’s findings are grounded in agency theory. Using purposive sampling, 179 observations were selected. The Net Profit Margin (NPM) Index is employed as a proxy for tax aggressiveness, and the data were analyzed using multiple linear regression via the EVIEWS 13 software. The findings indicate that profitability significantly affects tax aggressiveness, while liquidity and leverage do not.